Efficient Electrochemical Co-Reduction of Carbon Dioxide and Nitrate to Urea with High Faradaic Efficiency on Cobalt-Based Dual-Sites - Fan, Xiaoya (Advanced materials (Deerfield Beach, Fla.), 2024)
© 2024 Wiley‐VCH GmbH.